Extraction and Enzymatic Assay of Glucose in Soils with Contrasting pH, Clay, and Organic Carbon Contents. Issue 3 (4th February 2020) - Liang, Zhi; Olesen, Jørgen E.; Nørgaard, Trine; Elsgaard, Lars
ABSTRACT: Glucose (C6 H12 O6 ) is common in soils and widely used as a model substrate to trace the turnover of dissolved organic carbon. Yet, challenges and limitations of extraction and direct quantification of glucose in divergent soils are poorly documented. Here we used a simplified procedure for extraction and enzymatic glucose quantification with 18 soils representing different pH, clay and organic carbon (OC) contents. Extracts were reacted for 30 min (20°C) with glucose oxidase, peroxidase, and o-dianisidine. The reaction was terminated with H2 SO4 and oxidized o-dianisidine was measured spectrophotometrically (540 nm). Recovery of glucose from mineral soils was not significantly affected by soil pH and OC, but decreased to 96% forincreasing clay contents (up to 45% clay). Extraction of soil in water (1:5, w/v) for 0.5 min was sufficient for sandy soils, whereas clayey soils were extracted for 5 min with benzoic acid (0.1%, w/v) as antimicrobial agent. Assays with organic soils (20% and 29% OC) showed that enzymatic glucose quantification was impeded presumably by extractable humic substances. It was possible to address this limitation with matrix-matched standard curves, but results from organic soils should be interpreted with care. The procedure had a detection limit of 1.5 µg g −1 soil and was applicable to small (1 g) soil samples allowing to trace the recovery and dynamics of glucose in time-course experiments. The procedure could also be applied to native soil samples in which case references for colorimetric background are prepared by adding H2 SO4 to the soil extract prior to the addition of assay reagents.